Implementasi Metode Fuzzy Mamdani Pada Alat Kesehatan Nirkabel Berbasis Android dan iOS - Ade Silvia Handayani; Elisa Islami Putri; Linda wati; Nyayu Latifah Husni; Hertani Indah Lestari; Moh Heri Kurniawan; Mega Hasanul Huda (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In today's technological developments, wireless communication provides many possibilities to be able to share information with each other anytime and anywhere and in various fields of life such as health services and the industrial world. One of the wireless communication technologies commonly used in health services is WBAN (Wireless Body Area Network), where WBAN (Wireless Body Area Network) can monitor a person's health condition anywhere and anytime by placing sensors around the body. In order for this monitoring process to be more effective and efficient, an application based on Android and IOS systems is designed that can display monitoring results in real time and can be used for patients or medical personnel. In addition, to minimize the performance of medical personnel in diagnosing patient conditions, an automatic diagnosis system is applied by utilizing fuzzy mamdani logic in making decisions from the measurement results obtained on the sensor.